Parque dos bichos na aldeia Vanuíre em Arco Íris-SP - Faccio, Neide Barrocá [UNESP] (2015)
This work is the result of studies and surveys did at the surroundings of the Vanuíre native village, placed in the municipality of Arco Íris, on the countryside of São Paulo State, which supported the development of projetual proposition meaning to foster the importance of the local culture throughout the implementation of a park with statues of animals from the regional fauna.